The relationship of obesity with falls among older adults / Kioh Sheng Hui - Kioh, Sheng Hui (2021)
Both falls and obesity are major public health issues in older adults and have been identified as the fifth leading cause of death among older adults. The relationship between obesity and falls have been conflicting in the limited publications available. This doctoral research comprised: 1) a cross-sectional study on obesity and falls, 2) a prospective study on obesity and falls and 3) an intercontinental comparison of relationship between obesity and falls. The study populations consisted of adults aged ≥55years from the Malaysian Elders Longitudinal Study (MELoR), the European Prospective Investigation into Cancer - Norfolk study (EPIC- NORFOLK) and Bavarian Research Foundation-Sarcopenia and Osteoporosis study (FoRMOSA). Body mass index (BMI), waist circumference (WC), waist hip ratio (WHR) and percentage body fat (%BF) were associated with falls. Body composition contributed to 69% of the association between BMI and falls. Prospective analyses revealed WHR was a stronger risk factor compared to BMI, WC and %BF. International comparisons found significant associations between BMI and falls in both Caucasians and Asians. BMI remained as an independent risk factor for falls among Caucasians but not Asian upon adjusting for body composition. In conclusion, this study has provided new knowledge on obesity and falls in challenging the value of BMI, with WHR proposed as a suitable alternative. In the interim, our findings may assist health professionals and policy makers with the formulation of culturally relevant and targeted fall prevention interventions to prevent falls among older adults with obesity. Keywords: Accidental Falls, Anthropometric, Obesity, Cultural, Older Adults